Hubungan Upah dan Penawaran Tenaga Kerja Supir Taxi di Surabaya - Solihin, Achmad; Sukartini, Ni Made (Jurnal Ekonomi Kuantitatif Terapan; 2014: Vol. 7, No. 1, Februari 2014 (pp. 1-82)DO - 10.24843/JEKT.2014.v07.i01.p07)
Utilizing 50 (fifty) of taxi drivers, who has been observing around 100 (one hundred) working days, this study exploring whether the prediction of Neoclassical theory or the Reference Dependence Point (RDP) about income targetting are followed by the taxi drivers in Surabaya city. Neoclassical theory assume that workers will respond positively with the transitory wage change, while the Reference Dependence Point, especially income targetting predict there is negative relationship between labor supply and positive wage income transitory. RDP theory predict that workers will decide reducing their working hours or stopping to work when their wage income has exceed their targetted income. Most of the previous studies evaluate the RDP hiphotesis on taxi drivers. In this study we find that among 50 (fifty) taxi drivers being observed in Surabaya following the prediction of RDP theory. The point elasticity of labor supply in respond to positive wage changing has been found on the range of -0.004 % to -0.0012%.
Keywords: Taxi Driver , income targeting , change in labor supply , Surabaya city